5x-9-2x+3=

Simple and best practice solution for 5x-9-2x+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-9-2x+3= equation:


Simplifying
5x + -9 + -2x + 3 = 0

Reorder the terms:
-9 + 3 + 5x + -2x = 0

Combine like terms: -9 + 3 = -6
-6 + 5x + -2x = 0

Combine like terms: 5x + -2x = 3x
-6 + 3x = 0

Solving
-6 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 3x = 0 + 6
3x = 0 + 6

Combine like terms: 0 + 6 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| f+(-7)=9 | | 12m+53=173-8m | | -3x+6-4x=41 | | 2x^2-26x+84= | | 2x+148.50=4651.50 | | a/2=30 | | 5=2x+5x+5 | | y=(0.5x^3)-(2x^2)-(3x)+4 | | 3(X-5)+4(2X+1)=9 | | 3x^2-32x-11= | | H(x)=-16x^2+16x+5 | | v^2-2v+8=0 | | 9x+y=11 | | 15b^2+12b^3= | | (-10)(3000)= | | 4y^2+3x-24y-12=0 | | 12m-13=9m+38 | | 57+12m=7m+149 | | 13x+1=5x+49 | | 97+13m=5+17m | | 8y^2-y=-9 | | 11x=3x-56 | | 3x+9-7x=33 | | 5-y=10y-40 | | -3=4(-3)+6-(-3) | | 141000000/1.17 | | 6x+2-3x+2=9x-12 | | 9-5/3b=3 | | 2x^2-8x+8=98 | | 5(2+X)=3x-4 | | x^2/4x | | u^2-10u-21=0 |

Equations solver categories